Conservation status of water and permanent preservation areas in the Cabaçal river basin, Mato Grosso state, Brazil - Galvanin, Edinéia Aparecida dos Santos [UNESP]; Lorenzon, Thiziane Helen; Neves, Sandra Mara Alves da Silva; Filho, Luiz Carlos Machado (Elsevier, 2024)
The impairment of natural resources by misuse of the land is reflected in the quality of water bodies and conservation of vegetation cover. The objective of this study was to quantify the level of conservation of vegetation in the Cabaçal river basin in the Brazilian Mato Grosso state. The methodological procedures consisted of digital image processing in a Geographic Information System and physical-chemical analysis of water. This procedure was adopted to quantify the levels of water quality and conservation. Those sections with vegetation in the areas of permanent preservation (APPs) of the basin correspond to 53.16% while the agricultural activities to 43.86%, meeting what was established by the Complementary Law Nr.432/2010 of Mato Grosso State. All the five sub-basins analyzed presented a Water Conservation Index classified as High. However, the sub-basins Rio Branco and Rio dos Bugres were the most affected, with less than 50% of its conservation area. The sub-basin Interbacia do Rio Cabaçal showed the best conservation index due to higher Water Quality Index values and has almost 55% of its APPs preserved. The results were affected by seasonality which was better during the dry season. It was concluded that the commitment of the vegetation cover in Permanent Preservation Areas of subbasins from Cabaçal river basin and the values of the Water Quality Index negatively influenced those conservation rates from the subbasins analyzed.
Keywords: Conservation indicator; Environmental planning; Vegetation; Water quality